Non-neoplastic Polyps of the Gallbladder: A Clinicopathologic Analysis of 447 Cases. (April 2020) - Taskin, Orhun C.; Bellolio, Enrique; Dursun, Nevra; Seven, Ipek Erbarut; Roa, Juan C.; Araya, Juan C.; Villaseca, Miguel; Tapia, Oscar; Vance, Courtney; Saka, Burcu; Balci, Serdar; Bagci, Pelin; et al.
Abstract : There is no systematic histopathologic analysis of non-neoplastic polyps in the gallbladder. In this study, in addition to a computer search for cases designated as "polyp, " a systematic review of 2533 consecutive routinely sampled archival and 203 totally submitted prospective cholecystectomies were analyzed for >2 mm polyps (cut-off was based on radiologic sensitivity). A total of 447 non-neoplastic polyps were identified. The frequency was 3% in archival cases and 5% in totally submitted cases. Only 21 (5%) were ≥1 cm. The average age was 52 years, and the female to male ratio was 3.1. Two distinct categories were delineated: (1) injury-related polyps (n=273): (a) Fibro(myo)glandular polyps (n=214) were small (mean=0.4 cm), broad-based, often multiple (45%), almost always (98%) gallstone-associated, and were composed of a mixture of (myo)fibroblastic tissue/lobular glandular units with chronic cholecystitis. Dysplasia seen in 9% seemed to be secondary involvement. (b) Metaplastic pyloric glands forming polypoid collections (n=42). (c) Inflammatory-type polyps associated with acute/subacute injury (11 granulation tissue, 3 xanthogranulomatous, 3 lymphoid). (2) Cholesterol polyps (n=174) occurred in uninjured gallbladders, revealing a very thin stalk, edematous cores devoid of glands but with cholesterol-laden macrophages in 85%, and cholesterolosis in the uninvolved mucosa in 60%. Focal low-grade dysplasia was seen in 3%, always confined to the polyp, unaccompanied by carcinoma. In conclusion, non-neoplastic polyps are seen in 3% of cholecystectomies and are often small. Injury-related fibromyoglandular polyps are the most common. Cholesterol polyps have distinctive cauliflower architecture, often in a background of uninjured gallbladders with cholesterolosis and may lack the cholesterol-laden macrophages in the polyp itself. Although dysplastic changes can involve non-neoplastic polyps, they do not seem to be the cause of invasive carcinoma by themselves.